ANALISIS PENGARUH USIA DAN STATUS PERNIKAHAN TERHADAP KINERJA KARYAWAN PT. GLOFIN KEBAKKRAMAT KABUPATEN KARANGANYAR - Budiwinarto, Kim; Susilowati, Susilowati (Surakarta Management Journal, 2021)
The purpose of this study was to determine the effect of age and marital status on the  employees performance of PT. Glofin Kebakkramat, Karanganyar Regency. The data needed in this study is primary data in the form of respondents' assessments of age, marital status, and employee performance. In this study, a sample of 80 respondents was taken. The data collection method used a questionnaire. The data analysis used in this study is multiple linear regression analysis, t test, F test, and the coefficient of determination. Analysis of employee performance in the morning shift found that age has no effect on the employees performance  of PT. Glofin Kebakkramat, Karanganyar Regency, while marital status has an effect on the employees performance of PT. Glofin Kebakkramat, Karanganyar Regency. Analysis of employee performance in the day shift found that age affects the employees performance of PT. Glofin Kebakkramat, Karanganyar Regency, and marital status affects the employees performance of PT. Glofin Kebakkramat, Karanganyar Regency. Analysis of employee performance on night shifts shows that age does not affect the employees performance of PT. Glofin Kebakkramat, Karanganyar Regency, while marital status affects the employees performance of PT. Glofin Kebakkramat, Karanganyar Regency. Keywords: age, marital status, employee performance